Penerimaan Beasiswa KIP Untuk Calon Mahasiswa Di Universitas - Irvan Malay; Syahrial Hasanuddin Pohan; Dika Ryanda (GLOBAL SCIENTS PUBLISHER, 2026)
The selection process for the Kartu Indonesia Pintar (KIP) College scholarship requires an objective and transparent assessment. This study aims to apply the Mamdani Fuzzy Inference System (FIS) to optimize accuracy and simplify the scholarship selection process for prospective students. Modeling was conducted using Microsoft Excel with two input variables—Report Card Grades (NR) and Academic Potential Test (TPA) scores—and one output variable, the Admission Decision. Evaluation involved 12 rule bases using MIN-MAX operators and defuzzification via the Centroid method on 38 student data samples. Results show that the Mamdani FIS successfully classified graduation levels precisely into final recommendations: